Critical success factor within family business in Malaysia - K. Ramachandran, Pakiam (2021)
Business performance plays an important role in all types of business whether its general business, SME business or family business. There are various studies conducted to measure the critical success factors for a business but there are limited studies conducted to identify the other critical success factors within family business in Malaysia context. The lack of quantitative research on the family business was the main reason for the present research in identifying the critical success factors withing family business in Malaysia. This research was guided by the following research problem: “How and why the critical success factors can be established within family business in Malaysia?” The literature review on the critical success factor within family business identified three research problem. For investigate the issues, a qualitative study was conducted, and the respondents were identified by using snowballing sample technique. Convergent interview was conducted to confirm the critical success factors within family business in Malaysia and the data were analyzed using content analysis techniques. The research findings confirmed 9 critical success factors within family business in Malaysia i.e., management support & know-how, customer involvement & market knowledge, information system/advance technology, sales & profitability/ company performance, teamwork/cooperation, innovativeness & product differentiation, strategic alliance, commitment/hardworking and mentoring process. There are four new emerging factors i.e., family support, time management, location/environment of a business and business reputation which demonstrates the present research’s contribution to the body of knowledge. The revised theoretical framework built from the theories and literature review provides the foundation for future research.